TRẠNG THÁI ỨNG SUẤT KIẾN TẠO HIỆN ĐẠI KHU VỰC BỂ CỬU LONG - Hướng, Nguyễn Văn; Trịnh, Phan Trọng; Đang, Hoàng Ngọc (Vietnam Journal of Earth Sciences, 2012)
SUMMARY Present-day stress state in Cuu Long basin Indicators of maximum horizontal compressive stress (SHmax) orientation can be compiled from various sources of data such as fault slip, volcanic-vent alignment, earthquake focal mechanisms and boreholes. Our work concentrates on analysis of all available borehole images from petroleum exploration in Cuu Long basin, offshore southern Vietnam to find BOs and DIFs and to analysis perturbation of SHmax orientation with regard to relative motion vector between Yangtze block and Sundaland block in MORVEL model. It is showed that SHmax orientation in Cuu Long basin varies from NNW-SSE to NW-SE direction which is consistent with regional stress. Contrary to significant clockwise rotation in Nam Con Son basin, average SHmax orientation in Cuu Long basin is gently anti-clockwise rotated with regard to MORVEL. It is also existed the difference of SHmax orientation between the north part of Cuu Long basin and the rest. Orientation of SHmax in the north part is gently anti-clockwise while the rest has no rotation with regard to MORVEL.